Hydrate occurrence identification of shallow loose sediments in deep water and its saturation calculation - Jun Zhao; Chao Zheng; Jianxiang Pei; Di Tang; Jiang Jia (Journal of Natural Gas Geoscience)
The Chinese offshore area holds vast reserves of deepwater and shallow gas hydrates. However, due to the geological looseness of deepwater and shallow layers, the absence of tight sealing layers, and the high heterogeneity of gas hydrate reservoirs, identifying the occurrence state of gas hydrates remains challenging, greatly impeding the accurate prediction of gas hydrate saturation. Based on the acoustic-electric response characteristics of deepwater and shallow gas hydrates, this study employs the intersection method of resistivity and longitudinal wave velocity diagrams to identify the occurrence state of gas hydrates. The pore volume of gas hydrate reservoirs is calculated using a density formula corrected for mud content. Gas hydrate saturation in the YL target area of the Qiongdongnan (QDN) Basin is predicted using three methods: the mud-corrected resistivity method, the equivalent medium method, and the joint inversion method, finding the minimum combined error of acoustic and electric data. The results indicate that the predicted values using the joint inversion method in the YL target area of the QDN Basin are closest to the measured values obtained from the chloride ion concentration method, with prediction errors ranging from 0.09 % to 14.89 % and an average error of 6.85 %. These findings suggest that selecting an appropriate acoustic-electric joint inversion saturation calculation model, based on the determination of hydrate occurrence states, can significantly improve the accuracy of hydrate saturation prediction. This approach provides a realiable method for calculating hydrate saturation in the deepwater and shallow sediments.